Antimicrobial phenolic metabolites from the aerial parts of Orthosiphon aristatus. (December 2022) - Tung, Nguyen Ngoc; Tam, Le Thi; Anh, Do Hoang; Hanh, Tran Thi Hong; Cuong, Nguyen Xuan; Cuong, Nguyen The; Quang, Tran Hong
Abstract: Two new compounds oraristatin A (1 ) and oraristatinoside A (2 ), one new natural compound (2  S )-methyl-6, 7-dihydroxytropate (3 ), and 11 known phenolic metabolites were isolated from the aerial parts of Orthosiphon aristatus . Their chemical structures were identified by 1D- and 2 D NMR and HRESIMS spectroscopic analyses. The absolute configurations of 1 and 3 were determined by TD-DFT ECD spectroscopic analyses. Of the isolates, compound 2 weakly inhibited both Gram-positive and -negative bacteria (MIC = 150–300 μM), while 6 and 7 suppressed the growth of three Gram-positive bacteria and a yeast (MIC = 75–150 μM). This is the first report of the isolation of 6 − 9, 12, and 14 from the genus Orthosiphon and the antimicrobial effects of compounds 3, 7, 9, 12, and 14 . Graphical Abstract: ga1 Highlights: 14 compounds were isolated from Orthosiphon aristatus. Two new, one new natural, and 11 known compounds were structurally elucidated. Antimicrobial effects of extract, fractions, and compounds were evaluated.